Continuous gas-phase oxidation of methane into methanol over Cu-mordenite - Xu, Zhenchao; Kang, Jongkyu; Park, Eun Duck (Microporous and Mesoporous Materials, 2023)
The direct conversion of methane into methanol is an ideal, highly promising process; however, its application remains challenging. Herein, a systematic study was carried out on the continuous gas-phase oxidation of methane into methanol with steam in the absence and presence of O2 over Cu-mordenites (Cu-MOR) with various Cu loadings. The methanol productivity depended on the Cu/Al ratio of the Cu-MOR; it could be maximized by selecting the optimum Cu/Al ratio. Methanol productivity increased as the concentration of O2 in the feed increased from 0 to 100 ppm. However, methanol selectivity decreased when the O2 concentration in the feed was above 25 ppm. The stable methanol production rates based on the Cu content were 0.14 and 0.70 mol CH3OH/mol Cu/h at 400 °C over a Cu-MOR catalyst with 6.2 wt% Cu under anaerobic conditions and one with 3.0 wt% Cu in the presence of 25 ppm O2, respectively.
Keywords: Continuous gas phase; Conversion of methanes; Cu-mordenite; Direct conversion; Gas phase oxidation; ITS applications; Methane activation; Methane selective oxidation; Mordenites; Oxidation of methane; Cu-mordenite; Gas-phase oxidation; Methane activation; Methane selective oxidation; Methanol